Reflections on Sociology of Law in Law Enforcement in society - Hartanto (Journal of Legal and Cultural Analytics, 2023)
Sociology cannot be used directly in the context of distorting the scope of legal science in its independent substance, legal sociology is a middle way with its various slices. The complex reality in society provides many distortions as to whether law can be independent or a truly substantially open system, in the midst of our legal development position which was previously the perspective of Dutch scientists and is currently required to accommodate "laws that live in society", let alone coincide with the current social conditions of people who are trying to become survivors amid the Covid-19 pandemic and the new normal era, in this case social reality requires the role of law. So the role of the sociology of law in law enforcement in society is urgently needed, in this study law is not an autonomous institution but is interdisciplinary in dealing with social phenomena to realize people's welfare. Law enforcement in society is an effort to realize respect for social norms, through legal reform must include preventive and repressive stages of improvement, improvement of morality, behavior of law enforcement officials, and as the most important element is community involvement.